A Novel Mutation of ALDH5A1 Gene Associated With Succinic Semialdehyde Dehydrogenase Deficiency. (March 2015) - Lin, Chun-Yen; Weng, Wen-Chin; Lee, Wang-Tso
Succinic semialdehyde dehydrogenase deficiency is a rare autosomal recessive metabolic disorder affecting γ-aminobutyric acid degradation. We described a boy with a severe phenotype of succinic semialdehyde dehydrogenase deficiency and novel mutations of ALDH5A1 gene. He was referred because of developmental delay, focal seizures, and choreoathetosis at 6 months of age. The diagnosis of succinic semialdehyde dehydrogenase deficiency was confirmed by increased level of γ-hydroxybutyric acid in urine and novel compound heterozygous mutations in the ALDH5A1 gene. His seizures were successfully controlled. However, the patient showed a slowly progressive clinical course with severe neurologic deficits. A magnetic resonance imaging (MRI) revealed abnormal high intensities in the putamen and globus pallidi on T2-weighted images when he was 6 months old, and more diffuse abnormal signal intensities over bilateral hemispheres were noted when he was 3 years old.